THE DYNAMICS OF SOCIAL ECONOMIC LIFE OF MOTOR RICKSHAW DRIVERS AMID THE DEVELOPMENT OF ONLINE TRANSPORTATION IN MAKASSAR CITY - Mardania, Mardania (Universitas Negeri Makassar, 2022)
This study aims to (1) describe the dynamics of the socio-economic life of motorized rickshaw riders in the city of Makassar (2) find out the problems caused by online transportation to the life of online transportation in Makassar City. The type of research used in this research is descriptive qualitative. The data collection techniques in this study were using the methods of observation, interviews, and documentation, then analyzed with qualitative descriptive techniques. The results showed that (1). The description of the dynamics of the socio-economic life of motorized rickshaw drivers in Makassar City, namely work, income, education and family. The work is categorized as